2019
DOI: 10.1101/590653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cultivatingin situtriggers growth of previously uncultivated microorganisms via a growth initiation factor in nature

Abstract: Most microorganisms resist cultivation under standard laboratory conditions. On the other hand, to cultivate microbes in a membrane-bound device incubated in nature (in situcultivation) is an effective approach. In the present study, we appliedin situcultivation to isolate diverse previously uncultivated marine sponge-associated microbes and comparatively analyzed this method’s efficiencies with those of the conventional method. Then, we attempted to clarify the key and unknown mechanism ofin situcultivation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 76 publications
2
6
0
Order By: Relevance
“…The ratio was calculated using the average value from triplicate measurements (n=3) of the CFUs on each agar plate. Data for SDP strains have already been reported (Jung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The ratio was calculated using the average value from triplicate measurements (n=3) of the CFUs on each agar plate. Data for SDP strains have already been reported (Jung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We refer to isolates from SDP cultivation performed in the same series of experiments (Jung et al, 2021) using the same sample. SDP cultivation resulted in isolates representing 13 species from three taxonomic groups (Bacteroidetes, Alphaproteobacteria and Gammaproteobacteria; Figure 3, Table S3).…”
Section: Identification Of Isolated Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The sponge holobiont evolved in intricate association with microorganisms and numerous modes of interaction have been identified that mediate between microorganisms and their sponge host. For example, sponge extract seems to contain chemical compounds that facilitate bacterial starvation recovery (Jung et al, 2019). Proteins involved in eukaryote-prokaryote interactions such as eukaryotic-like proteins (ELPs), ankyrin repeats (ANKs) and tetratricopeptide repeats (TPRs) are regularly detected in sponge-associated bacteria and have been shown to modulate phagocytosis by amoebal cells (Nguyen et al, 2014;Reynolds & Thomas, 2016).…”
Section: Focus On the Sponge Hostmentioning
confidence: 99%